ECTHR_COMMITTEE 8974/22 vom 30. April 2026 , AFFAIRE VOZDEYEVA c. RUSSIE - Ecthr Committee (2026)
Violation de l'article 2 - Droit à la vie (Article 2-1 - Enquête effective) (Volet procédural); Violation: 2;2-1